AB0755 REAL WORLD EFFECTIVENESS OF SECUKINUMAB IN PSORIATIC ARTHRITIS: FINDINGS FROM A RECENT CROSS SECTIONAL SURVEY OF RHEUMATOLOGISTS AND PATIENTS IN EUROPE. (2nd June 2020) - Conaghan, P. G.; Holdsworth, E.; Tian, H.; Booth, N.; Anthony, P.; Modi, N.; Keininger, D.; Kiltz, U.
Abstract : Background: Secukinumab has demonstrated significant and sustained reduction of disease activity and improvement in physical functioning and quality of life in PsA pts in RCTs. 1 Objectives: This study assessed effectiveness of secukinumab in PsA in a real-world setting. Methods: This was a cross-sectional survey of rheumatologists, dermatologists and pts in France, Germany, Italy, Spain, and UK. Data were collected online from June-Dec 2018 via physician-completed patient record forms. Pts receiving any treatment for PsA were included in survey (n=1675). Pts receiving secukinumab >4 months were included in this analysis. Pts reported quality of life, work, and disability measures at their current consultation. Physicians reported patient demographic and disease characteristics, concomitant and previous treatments, and time since diagnosis. Physicians also reported overall, skin and joint disease severity, pain (1-10 scale), BSA psoriasis involvement, global VAS score, PASI score, SJC, and TJC for 2 time points: initiation of treatment and at the time of data collection (current consultation). Data were analysed descriptively. The data analysed here is representative of pts that are currently receiving secukinumab and does not assess pts that have discontinued treatment. Results: 572 PsA pts were receiving secukinumab >4 months at their current consultation. Patient mean age was 47.9 yrs, with 43% female, 59% working full time, and a mean BMI of 26.6. On average, pts were diagnosed with PsA 5.6 years before the current consultation, had received secukinumab for 11.0 months, and for 59% of pts secukinumab was their 1st advanced therapy (bDMARDs or tsDMARDs), 24% their 2nd and 16% their 3rd or more. 25% of pts were also receiving a csDMARD concurrently. Pts reported a mean EQ5D utility score of 0.83, mean WPAI overall work impairment of 24.3%, mean HAQ-DI score as 0.6, and mean PsAID12 score as 2.6 at current consultation. Proportion of pts with moderate and severe overall disease severity, and skin and joint severity decreased at current consultation vs at the initiation treatment (Table 1). Between initiation of treatment and current consultation, pts achieved a significant reduction in disease activity scores, pain score, global VAS scores, BSA, PASI score as well as a greater proportion of pts achieving a BSA < 3%, a PASI score < 3 (Table 2). Conclusion: This multinational study demonstrated secukinumab effectiveness in routine care in PsA pts, with significant improvements across all outcomes. References: [1]Mease et al. RMD Open. 2018; 4(2): e000723 Disclosure of Interests: Philip G Conaghan Consultant of: AbbVie, BMS, Eli Lilly, EMD Serono, Flexion Therapeutics, Galapagos, GSK, Novartis, Pfizer, Speakers bureau: AbbVie, Eli Lilly, Novartis, Pfizer, Elizabeth Holdsworth Employee of: Adelphi Real World, Haijun Tian Shareholder of: Novartis Pharmaceutical Corporation, Employee of: Novartis Pharmaceutical Corporation, Nicola Booth Consultant of: Janssen, Papa Anthony: None declared, Niraj Modi Employee of: Novartis Healthcare Pvt Ltd, Dorothy Keininger Shareholder of: Novartis Pharma AG, Employee of: Novartis Pharma AG, Uta Kiltz Grant/research support from: AbbVie, Amgen, Biogen, Novartis, Pfizer, Consultant of: AbbVie, Biocad, Eli Lilly and Company, Grünenthal, Janssen, Novartis, Pfizer, UCB, Speakers bureau: AbbVie, MSD, Novartis, Pfizer, Roche, UCB